Molecular insights of a novel fish Toll-like receptor 9 homologue in Nibea albiflora to reveal its function as PRRs. Issue 118 (November 2021) - Liu, Huihui; Yang, Meijun; Tang, Xiuqin; Liu, Jiaxin; Zheng, Libing; Xu, Dongdong; Chi, Changfeng; Lv, Zhenming
Abstract: Toll-like receptors (TLRs) are an important class of molecules involved in non-specific immunity, and they are also the bridge connecting between non-specific immunity and specific immunity. As a vital member of TLR family TLR9 can be activated by bacterial DNA and induce the production of inflammatory cytokines. In this study, a full length of TLR9 homologue of 3677 bp in Nibea albiflora (named as NaTLR9, GenBank accession no: MN125017.1) was characterized, and its ORF was 3180 bp encoding 1059 amino acid residues with a calculated molecular weight of 121.334 kDa ( pI = 6.29). Several leucine-rich repeated sequences (LRR domain) and conservative TIR domain were found in NaTLR9, which was mainly expressed in dendritic cells and macrophages. The phylogenetic and synteny analysis further revealed high sequence identity of NaTLR9 with its counterparts of other teleost, confirming their correct nomenclature and conservative during evolution as an important pattern recognition receptor. The NaTLR9-TIR-pEGFP-N1 fusion protein showed green fluorescence and mainly distributed in the cytoplasm. After co-transfection of NaTLR9-TIR-pEGFP-N1 and NaMyD88-pDsRED-Monomer-N1, green fluorescence obviously overlapped with red and changed into yellowish-green, which suggested that there might be the interaction between homologous NaTLR9-TIR and MyD88. Based on this result the pCDNA3.1-NaTLR9-TIR-flag and pcMV-NaMyD88-TIR-Myc plasmids were co-transfected into 293T cells for the immunoprecipitation test. According to Western blot, TLR9 and MyD88 protein could interact with each other. Furthermore, NaTLR9 was ubiquitously expressed in all the investigated tissues, most abundantly in head kidney, followed by stomach, spleen, liver and gill, but lower in muscle. The vitro immune stimulation experiments revealed that Pseudomonas plecoglossicida and polyinosinic-polycytidylic acid [Poly (I:C)] induced higher levels of NaTLR9 mRNA expression with the peaks of 9.52 times at 2 h and 39.91 times at 24 h compared with the control group respectively. The functional domains (LRRs and TIR, named NaTLR9-TIR and NaTLR9-LRR respectively) of NaTLR9 were expressed and purified, the recombinant proteins both could bind three kinds of typical aquatic pathogenic bacteria ( Vibrio. parahaemolyticus, Vibrio alginolyticus, and Vibrio harveyi ), which showed that NaTLR9 could couple to bacteria by its function domains. The aforementioned results indicated that NaTLR9 played a significant role in the defense against pathogenic bacteria infection in innate immune response of sciaenidae fish, which may provide some further understandings of the regulatory mechanisms in the teleostean innate immune system. Highlights: A TLR9 homologue was identified from Nibea albiflora (NaTLR9). The functional domains in NaTLR9 were highly conserved and located in cytoplasm. There was the interaction between NaTLR9 and MyD88 for Toll/NF-κB pathway. NaTLR9 could be significantly induced in response to bacteria and viruses infection. NaTLR9 could couple to the pathogenic bacteria.